Filsafat Islam dalam Prespektif Sejarah: Telaah Kritis Pemikiran Henry Corbin dalam Buku History of Islamic Philosophy - Ulfi Maula Saniya; Hanafi, Yusuf (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Islamic philosophy is one of the most dynamic intellectual traditions in the history of Islamic civilization, but its development is often reduced in modern historiographical narratives that place it as a continuation or derivative of Greek philosophy alone. Through his work History of Islamic Philosophy, Henry Corbin offers a different hermeneutic and phenomenological framework for reading the development of Islamic philosophy, namely by placing it as a continuous tradition, spiritual-metaphysical in nature, and not limited by political boundaries or conventional chronological sequences. This article aims to critically examine Corbin's view of the continuity of Islamic philosophy, assess his intellectual contribution to the study of Islamic philosophy, and examine the methodological limitations of his approach. Through a literature review and content analysis of Corbin's book and relevant academic literature, this article finds that Corbin has succeeded in opening new horizons in understanding the richness of the Islamic intellectual tradition, particularly through his emphasis on the role of creative imagination, inner dimensions, and the continuity of the wisdom tradition in Iran. On the other hand, his tendency to focus on esoteric aspects and spiritual experiences makes his narrative less comprehensive in reaching the rational, political, and social traditions in Islamic philosophy. This article concludes that despite its limitations, Corbin's work still makes a significant contribution to the development of contemporary Islamic philosophy studies, particularly in establishing a more holistic, dialogical, and open approach to the metaphysical dimensions of Islamic tradition.